HUMAN CAPITAL DEVELOPMENT FOR CYBERSECURITY : ExaminingBSSN's Contributions in the Indonesia-Australia Cyber PolicyDialogue (2018-2020) - Muhammad Rafi Shiddique, (The Asian Institute of Research, 2023)
The rapid development of technology poses threats in cyberspace, including in Indonesia. This type of threat is relatively new to Indonesia, especially since 2020. One of the challenges faced by Indonesia in dealing with cyber threats is the need for more competent human resources. In 2018, Indonesia and Australia collaborated in the form of the Indonesia-Australia Cyber Policy Dialogue, one of which is Capacity Building and Strengthening Connection. This research aims to discover how the Indonesian government, through BSSN, improves human resources by cooperating with Australia. The author uses a qualitative approach and descriptive research type in this research. The author also uses the concepts of international cooperation and cybersecurity to analyze this problem. The results of this study show that through BSSN, Indonesia has great potential to improve national cyberspace because it gets direct knowledge and practice from Australia. The potential of BSSN is expected to answer the need for more competent human resources in Indonesia to secure national cyberspace.